1989
DOI: 10.4025/jphyseduc.v32i1.3237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training session on mood state responses in athletes of wheelchair basketball team

Abstract: The assessment of mood state can be used as a tool for monitoring the training adaptation. However, to athletes with a physical disability, this tool is still a few explored, especially in training daily conditions. The aim of the study was to analyze the mood state during training sessions in wheelchair basketball athletes. Twelve male athletes, aged between 23 and 62 years old, were evaluated. The subjects answered the POMS questionnaire before and after five training sessions during the preparatory period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Then Selmi et al [15], in his research explained that MS was influenced by several factors such as family or school. MS has an important role for studentathletes in following the PE process optimally in the long term, because positive MS has the potential to reduce levels of burnout, depression [16], stress [17,18], anger [19], on the other hand studentathletes with negative MS tend to have a low level of involvement in learning activities [20,21,22]. A previous study has confirmed that the benefits of MS can trigger enthusiasm in studentathletes to achieve a goal in the context of physical education [23], or sports [24].…”
Section: Introductionmentioning
confidence: 99%
“…Then Selmi et al [15], in his research explained that MS was influenced by several factors such as family or school. MS has an important role for studentathletes in following the PE process optimally in the long term, because positive MS has the potential to reduce levels of burnout, depression [16], stress [17,18], anger [19], on the other hand studentathletes with negative MS tend to have a low level of involvement in learning activities [20,21,22]. A previous study has confirmed that the benefits of MS can trigger enthusiasm in studentathletes to achieve a goal in the context of physical education [23], or sports [24].…”
Section: Introductionmentioning
confidence: 99%